DISPENSARY CONTROL OF CHILDREN WITH CONGENITAL DEFECTS IN THE MAXILLOFACIAL SYSTEM ARRANGE TO RECEIVE. (Multidisciplinary Journal of Science and Technology, 2024)
In this article, dispensary control of children with congenital defects in the maxillofacial system is described in the organization of the reception. Babies born with congenital defects in the area of the face and jaws should receive preventive and effective specialized complex treatment under the supervision of a local (city, district) pediatric dentist and be monitored until the age of 14-15.